18th International Working Conference on Requirements Engineering: Foundation for Software Quality. Proceedings of the Workshops RE4SuSy, REEW, CreaRE, RePriCo, IWSPM and the Conference Related Empirical Study, Empirical Fair and Doctoral Symposium - Richard Berntsson Svensson; Daniel Berry; Maya Daneva; Jörg Dörr; Samuel A. Fricker; Andrea Herrmann; Georg Herzwurn; Marjo Kauppinen; Nazim H. Madhavji; Martin Mahaux; Barbara Paech; Birgit Penzenstadler; et al. (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2012)
This ICB Research Report constitutes the proceedings of the following events which were held during the Requirements Engineering: Foundation for Software Quality (REFSQ) conference 2012 in Essen, Germany. Engineering for Sustainable Systems (RE4SuSy), Requirements Engineering Efficiency Workshop REEW 2012), Creativity in Requirements Engineering (CreaRE 2012), Requirements Prioritization for customer oriented Software Development (RePriCo), International Workshop on Software Product Management (IWSPM), Alive Empirical Study, Online Questionnaires, Empirical Research Fair, Doctoral Symposium.
Keywords: 650; Requirements Engineering; Softwareentwicklung; Betriebliches Informationssystem